2021
DOI: 10.1111/iju.14481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tadalafil versus silodosin on voiding function in male patients with non‐neurogenic detrusor underactivity: A comparative study using propensity score matching

Abstract: To investigate and compare the effects of tadalafil and silodosin on lower urinary tract symptoms and voiding functions in men with non-neurogenic detrusor underactivity. Methods: A total of 126 treatment-naive men with lower urinary tract symptoms diagnosed as non-neurogenic detrusor underactivity received tadalafil (5 mg/day) or silodosin (8 mg/day) for 12 months. After propensity score matching, parameter changes from before administration to 12 months since treatment initiation were assessed based on subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The included studies, published between 2007 and 2021, [ 5 , 6 , 18 59 ] included 11 prospective studies [ 27 , 28 , 35 , 39 41 , 43 , 47 , 50 , 51 , 58 ], 2 retrospective studies, [ 36 , 37 ] and 31 RCTs. Thirty-four studies came from a single country, with Japan and Korea predominating, while the rest were multinational studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies, published between 2007 and 2021, [ 5 , 6 , 18 59 ] included 11 prospective studies [ 27 , 28 , 35 , 39 41 , 43 , 47 , 50 , 51 , 58 ], 2 retrospective studies, [ 36 , 37 ] and 31 RCTs. Thirty-four studies came from a single country, with Japan and Korea predominating, while the rest were multinational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Tables S3 and S4 present a full summary of the risk of bias for the included studies. Of the 13 observational studies, seven (54%) were of high quality [ 35 , 37 , 39 , 40 , 43 , 51 , 58 ] and the rest were of moderate quality; 46% of the observational studies did not mention adjustment for confounders [ 27 , 28 , 36 , 41 , 47 , 50 ]. The details of the 31 RCTs were as follows: (1) selection bias: 12 out of 31 studies reported the method of random sequence generation, [ 6 , 23 , 26 , 31 , 33 , 34 , 44 46 , 49 , 52 , 55 ] while the others did not.…”
Section: Resultsmentioning
confidence: 99%
“…The nitric oxide system has been of partial recent interest, with both tadalafil and silodosin demonstrating some benefits towards the reduction of lower urinary tract symptoms in men with non-neurogenic detrusor underactivity. 14 As more research is conducted into the mechanisms underlying bladder physiology, and the receptors involved, systems such as these may present opportunistic areas for future research. Of particular concern is the potential for high risk of bias within the literature.…”
Section: Discussion Evaluation Of the Literaturementioning
confidence: 99%
“…However, it remains unclear whether PDE5 inhibitors can be used as standalone treatments for DU. Recently, Matsukawa et al conducted a study that found that both tadalafil and silodosin had a significant impact on improving LUTS and voiding function in patients with non-neurogenic DU, and that tadalafil was associated with an improvement in BCI (19.7 ± 17.7 vs. 6.0 ± 12.5, p < 0.001) and Q max (3.0 ± 3.0 mL/s vs. 1.7 ± 1.4, p < 0.001) [116]. The mechanism of action of tadalafil may be linked to enhanced urethral relaxation [117], increased blood flow to the lower urinary tract [118], improved oxygenation [119], and decreased chronic inflammation [120] of the bladder and prostate.…”
Section: Phosphodiesterase 5 Inhibitors (Pde5is)mentioning
confidence: 95%